Development of Wireless Sensor Network (WSN) and Mobile Ad-Hoc Network (MANET) Communication for Military Operation and SAR (Search and Rescue) Operation - Nazri Ismail, Mohd; ‘Afizi Shukran, Mohd; Rizal Mohd Isa, Mohd; Adib, Mohd; Zakaria, Omar (International Journal of Engineering and Technology, 2018)
The study investigates and develops components for implementing an effective military and SAR (Search & Rescue) acknowledge/information/communication in closed network architecture. Since military and SAR personnel are always on the move, the dissemination of knowledge/information/communication needs a mobile platform to accommodate mobility of people. The mobile and wireless network platform should be able to sustain the remoteness and seclusion of military operation areas. Communication is one of key problems of a military operation especially due to environmental constraints. This study proposes on establishing a future soldier and SAR communication device with mobile Wireless Sensor Network (WSN) and Mobile Ah-Hoc Network (MANET) to suit the infantry operations in the urban and rural areas. The operational areas are considered to restricted and challenging locations. Wireless sensor network (WSN) and Mobile Ah-Hoc Network (MANET) will become inexpensive and common over the next decade Thus, a thorough study is vital to develop the most suitable smart equipment and network requirements for Malaysiaâ€™s military and SAR eco-system. Â Â Finally, this study has successfully developed new low cost device prototype using WSN and MANET approach for Military and SAR operation. This approach is able to transmit death and location status, movement location status, health monitoring status to the base Â station.Â Â